Contingency based congestion management and cost minimization using bee colony optimization technique - Rahim M.N.A.; Musirin I.; Abidin I.Z.; Othman M.M. (2023)
Unexpected contingency occurrence in a power system network can lead to high current flow in the system. This has made the system to be in a stressed condition which causes congestion to the system, while instability can be the next unpredictable incident. High current flow may also impose high fuel cost of the generators. Thus, congestion needs to be managed properly in order to reduce the undesired current flow in the transmission line for maintaining system security. This paper presents contingency based congestion management and cost minimization using bee colony optimization technique. In this study, bee colony optimization technique is applied to optimize the current flow in the system such that system security is preserved; considering transmission lines as the control variables. N-1 contingency is considered as the forecasted event, implemented offline so that the performance of the system can be evaluated. Cost minimization is also conducted by controlling the transmission constraints in the system. Validation through the IEEE 30-reliability test system and 6-Bus test system are conducted to simulate the scenarios. 2010 IEEE.